WEAR MECHANISM OF IRON COMPOSITE REINFORCED WITH SILICA - AMIR, ADIBAH (2016)
Wear results in severe economic loss and affected national income grossly. Therefore, efforts to develop wear resistant materials have been allotted a high priority in the field of materials research. The requirements for relatively inexpensive high wear resistance materials can be met simply and economically by producing iron base composite with silica reinforcement. This composite offers higher wear resistance and chemical stability at elevated temperature such as for high efficiency engines and turbo charger bushings application. The iron composites was fabricated via powder metallurgy technique, with five compositions of silica particles; 5, 10, 15, 20 and 25 wt.%. The sintering process was conducted using a Hot Isotatic Press at three sintering temperatures; 1000°C, 1100°C and 1200°C. Mechanical properties such as density, hardness and flexural strength were determined.